2019
DOI: 10.1037/pha0000253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and repeated treatment with serotonin 5-HT2A receptor agonist hallucinogens on intracranial self-stimulation in rats.

Abstract: The prototype 5-HT2A receptor agonist hallucinogens LSD, mescaline, and psilocybin are classified as Schedule 1 drugs of abuse by the U.S. Drug Enforcement Administration. Accumulating clinical evidence has also suggested that acute or repeated "microdosing" with these drugs may have utility for treatment of some mental health disorders, including drug abuse and depression. The goal of the present study was to evaluate LSD, mescaline, and psilocybin effects on intracranial self-stimulation (ICSS), a procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…But an important study showed that it can also modulate the sigma-1 receptor and therefore, indirectly affect Na + and K + channels (Fontanilla et al, 2009). Adding to the complexity of the mechanisms in which psychedelics affects the anxious brain, specific agonists of 5HT receptors do not seem to provide any beneficial effects in mood disorders (Sakloth et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…But an important study showed that it can also modulate the sigma-1 receptor and therefore, indirectly affect Na + and K + channels (Fontanilla et al, 2009). Adding to the complexity of the mechanisms in which psychedelics affects the anxious brain, specific agonists of 5HT receptors do not seem to provide any beneficial effects in mood disorders (Sakloth et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the acute administration of LSD, psilocybin, and mescaline fails to produce reliable evidence of abuse (Sakloth et al, 2019). Moreover, the authors found that repeated LSD (at the highest doses tested, but not at low doses) tends to attenuate the rewarding effects of the psychostimulant methamphetamine and the depressant k-opioid receptor agonist U69,593, although only findings for the latter were statistically significant (Sakloth et al, 2019).…”
Section: B Acute Side Effects Encountered In Uncontrolled Settingsmentioning
confidence: 98%
“…A rare case of physical dependence from, and tolerance to, LSD has recently been reported in the literature (Modak et al, 2019). One recent study investigated the abuse liability of low-and high-dose LSD, psilocybin, and mescaline and repeated LSD administration via the intracranial self-stimulation paradigm in rats, which is widely adopted to determine the abuse potential of a putative drug (Sakloth et al, 2019). Interestingly, the acute administration of LSD, psilocybin, and mescaline fails to produce reliable evidence of abuse (Sakloth et al, 2019).…”
Section: B Acute Side Effects Encountered In Uncontrolled Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 4 , 6 Moreover, preliminary findings and anecdotal reports suggest that psychedelics even show therapeutic potential in substance use disorders. 1 , 7 , 8 In addition, current research is investigating therapeutic applications of these substances in psychiatric disorders, with a focus on affective disorders. 8 11 While the intensity or quality of the psychedelic experience seems to contribute to its therapeutic effect, 12 anecdotal evidence also suggests that repeated use of smaller doses without the psychedelic experience (‘microdosing’) is efficacious self-treatment for people suffering from affective disorders.…”
Section: Introductionmentioning
confidence: 99%